Public Intention to Use EVs in East Java: Key Drivers - Sugeng Purwanto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This research examines the primary factors that influence public interest in adopting electric vehicles (EVs), with a particular focus on residents of East Java. Indonesia. Using a quantitative research design. data were gathered from 250 participants through a convenience sampling technique. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess construct validity and test the research hypotheses. The results indicate that four variables are perceived as ease of use, perceived usefulness, and green marketing. and perceived value each significantly and positively affect individuals’ intention to adopt EVs. These findings underscore the significance of personal perceptions and environmentally focused marketing strategies in promoting EV adoption on a practical level. The study provides valuable guidance for EV manufacturers in developing marketing strategies that emphasize user-friendliness, practical benefits, and environmental awareness. Overall. This research contributes to the literature on sustainable transportation by highlighting the crucial role of consumer perception and strategic messaging in promoting the adoption of electric vehicles, particularly in developing markets such as Indonesia.